Fitting Precipitation Variability in Dobrudja region - BĂRBULESCU, Alina; DEGUENON, AYICHEOU JUDICAËL TCHEDJI (My University, 2012)
An analysis of precipitation variability since 1965 has been carried out using annual and monthly data from Dobrudja, a region of situated in the South –East of Romania, between the Danube and The Black Sea. Performing the principal component analyses it has been proved that one of the series has a special behavior (due to its geographical position). Therefore, the annual precipitation evolution in the entire region can be modeled using the data provided by nine series, with small information loss. Finally, the regional precipitation evolution has been described by wavelets models using ten and nine series and the comparison between the results has been done.
Keywords: precipitation evolution; principal component analysis; wavelets